1975
DOI: 10.1042/bj1510603
|View full text |Cite
|
Sign up to set email alerts
|

The polypeptide composition of bovine epidermal α-keratin

Abstract: 1. The polypedtide chains that comprise the subunits of the tonofilaments, or th alpha-keratin component, of bovine epidermis were fractionated by combination of chromatography on DEAE-cellulose and preparative polyacrylamide-gel electrophoresis. 2. The seve polypeptide chains investigated had generalyy similar properties; all contained two residues per molecule of tryptophan and N-acetylserine was the common N-terminal amino acid residue. 3. On the basis of close similarities in alpha-helix content and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
73
1

Year Published

1979
1979
1996
1996

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(83 citation statements)
references
References 36 publications
9
73
1
Order By: Relevance
“…The IX-helical contents of components 5, 7 and 8 are 25 %, 45 % and 56 % respectively (Crewther et al 1968; Dowling unpublished data) and these are also similar to the values found for the three groups of polypeptide chains from bovine epidermal IX-keratin (Steinert and Idler 1975).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The IX-helical contents of components 5, 7 and 8 are 25 %, 45 % and 56 % respectively (Crewther et al 1968; Dowling unpublished data) and these are also similar to the values found for the three groups of polypeptide chains from bovine epidermal IX-keratin (Steinert and Idler 1975).…”
Section: Resultssupporting
confidence: 72%
“…The range of molecular weights (45000-60000) found for the polypeptide chains of the wool microfibril is comparable to that found for the IX-keratin from the filaments of bovine epidermis (Skerrow 1974;Lee and Baden 1976;Steinert and Idler 1975).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…These quantitative differences in the keratin content of the myoepithelial cells versus that in the other mammary epithelial cells, (ii) differences in keratin composition between species (mouse versus human) and between tissues (mammary gland versus epidermis), and (iii) recognition of different antigenic sites in the keratin polypeptides by the immune systems of the rabbit and guinea pig. Keratins from several species have been studied and shown to consist of multiple numbers of subunit polypeptides (3,(19)(20)(21). Differences in keratin composition are known to occur during the course of differentiation of epidermal cells (22)(23)(24), among different epidermal (21,25) and stratified squamous (26) epithelial cells of the same organism, and between fetal and adult tissues (27).…”
Section: Discussionmentioning
confidence: 99%